Cookeina colombiana (Sarcoscyphaceae, Ascomycota) a new species from the department Córdoba, Colombia - Raymundo, Tania; Montes-Fuentes, Gabriel; Valenzuela, Ricardo (Instituto de Ecología, A.C., 2020)
Background and Aims: The genus Cookeina is characterized by its brightly colored, stipitate or sessile apothecia, with or without hairs on the ectal excipulum, cylindrical and suboperculated asci and hyaline ascospores , smooth or with ornamentation. The genus is widely distributed and 18 species are known mainly from tropical and subtropical regions. Five species have been registered from Colombia: Cookeina colensoi, C. speciosa, C. sulcipes, C. tricholoma and C. venezuelae. The objective of this work is to describe and illustrate Cookeina colombiana, a new species from the department of Córdoba of the Colombian Caribbean region.Methods: The specimens were collected in tropical humid forest at the Ecological Station Las Guartinajas, in the department of Córdoba in Colombia. Field data and morphological characteristics were recorded according to traditional techniques in mycology. The material is deposited in the herbaria ENCB of the Escuela Nacional de Ciencias Biológicas of the Instituto Politécnico Nacional in Mexico, and HUC, of the Universidad de Córdoba, in Colombia.Key results: The new species Cookeina colombiana is described, characterized by the color of the apothecia on the hymenial surface, which are orange-brown, pale brown, brown to reddish brown, at the center dark brown to almost black in some specimens, and on the exterior surface pastel red, brown red, pale brown to reddish brown. It grows on decomposing wood of a eudicot tree.Conclusions: This species belongs to the Cookeina speciosa complex, characterized by a row of hairs on the edge of the apothecia and rows of hairs around the edge to the bottom, as well as by its setoid paraphyses. Cookeina colombiana is differentiated by the size of the ascospores, which are larger (35-37 × 14-17 µm) than those of C. speciosa (27.5-30 × 17-18 μm).